Clinical Significance of Credé's Prophylaxis in Germany at Present - Udo B. Hoyme (Hindawi Limited, 1993)
The introduction of silver nitrate for prophylaxis of gonococcal ophthalmia neonatorum is one of the milestones of preventive medicine. However, in our time an increasing necessity to review Credé's prophylaxis from both a human rights and a medical standpoint is required. The chairmen of the obstetrics and gynecology departments of the German university hospitals were questioned to learn about their policy and experience. Data were provided by 22 of 28 consulted institutions, representing 31,700 annual deliveries seen over a mean period of 5.5 years. Ocular prophylaxis was in use in 16 (73%) of the reporting hospitals (1% silver nitrate in 14 and gentamicin in 2). A nonspecific conjunctival reaction occurred in 5-10% of the newborns, but no major side effects were seen. Non-gonococcal ophthalmia neonatorum was observed in less than 0.1%; however, institutions without a preventive policy reported up to a 5% incidence of neonatal conjunctivitis, mostly due to Staphylococcus aureus, as well as Neisseria gonorrhoeae in two newborns. Application of silver nitrate is considered a necessary prophylactic measure and safe if it is properly administered. However, major efforts should be directed toward its replacement by alternative antiseptic substances as well as toward chlamydial screening and therapy in pregnancy.